Marijke van der Wal en Eep Francken, reds, Standaardtalen in beweging - Wąsik, Elżbieta (Department of Dutch and South African Studies, Faculty of English, 2011)
A review of Marijke van der Wal en Eep Francken, reds Standaardtalen in beweging Amsterdam: Stichting Neerlandistiek VU. 2010. 217 pp. ISBN 978-3-89323-763-0
Keywords: recenzja; review